The Validity of Direct Appointment Construction Contracts by State-Owned Enterprises to Their Subsidiaries After the Implementation of the Job Creation Law: A Study on Conflicts of Interest in the Procurement of Construction Consultancy Services Within PT PLN (Persero) - Aslihatin Zuliana; Iwan Erar Joesoef; Suherman Suherman (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the legal validity of direct appointment construction consultancy contracts between state-owned enterprises and their subsidiaries following the implementation of Indonesia's Job Creation Law. The research addresses critical questions regarding the formal legal mechanisms governing long-term unit-price framework agreements and their continued enforceability under amended procurement regulations. Employing a normative-jurisprudential methodology, the study systematically analyzes primary legal sources, including statutory provisions, government regulations, and corporate governance frameworks, alongside secondary legal materials and doctrinal commentaries. The analysis reveals that pre-Omnibus Law direct appointments complied with civil law contract validity requirements and sector-specific procurement regulations under Law No. 2/2017. Transitional provisions and the non-retroactivity principle preserved the enforceability of framework agreements executed prior to the Job Creation Law's enactment, while administrative amendments extending contract terms remained lawful under existing civil code provisions. The study demonstrates that direct appointment mechanisms achieve legal justification through constitutional mandates and legislative hierarchy, while providing utilitarian benefits through enhanced procurement efficiency and deployment of specialized technical expertise. The findings contribute to scholarly discourse on state-owned enterprise governance by elucidating how omnibus legislative reforms interact with contract doctrine and corporate governance norms, emphasizing the critical importance of robust conflict-of-interest safeguards in preventing procedural formalism from overshadowing substantive public interest outcomes.